Synergistic influences of introduced herbivores and fire on vegetation change in northern Patagonia, Argentina - Raffaele, Estela (2011)
Question: We investigated how cattle and European hares, the two most widespread exotic herbivores in Patagonia, affect species composition, life-form composition and community structure during the first 6 years of vegetation recovery following severe burning of fire-resistant subalpine forests and fireprone tall shrublands. We asked how the effects of introduced herbivores on post-fire plant community attributes affect flammability of the vegetation. widespread exotic herbivores in Patagonia, affect species composition, life-form composition and community structure during the first 6 years of vegetation recovery following severe burning of fire-resistant subalpine forests and fireprone tall shrublands. We asked how the effects of introduced herbivores on post-fire plant community attributes affect flammability of the vegetation. We investigated how cattle and European hares, the two most widespread exotic herbivores in Patagonia, affect species composition, life-form composition and community structure during the first 6 years of vegetation recovery following severe burning of fire-resistant subalpine forests and fireprone tall shrublands. We asked how the effects of introduced herbivores on post-fire plant community attributes affect flammability of the vegetation. Location: Nahuel Huapi National Park, northwest Patagonia, ArgentinaNahuel Huapi National Park, northwest Patagonia, Argentina Methods: We installed fenced plots to exclude livestock and European hares from severely burned subalpine forests of Nothofagus pumilio and adjacent tall shrublands of N. antarctica. The former is an obligate seed reproducer, whereas the latter and all other woody dominants of the shrubland vigorously resprout after burning. the latter and all other woody dominants of the shrubland vigorously resprout after burning. shrublands of N. antarctica. The former is an obligate seed reproducer, whereas the latter and all other woody dominants of the shrubland vigorously resprout after burning. the latter and all other woody dominants of the shrubland vigorously resprout after burning. from severely burned subalpine forests of Nothofagus pumilio and adjacent tall shrublands of N. antarctica. The former is an obligate seed reproducer, whereas the latter and all other woody dominants of the shrubland vigorously resprout after burning. the latter and all other woody dominants of the shrubland vigorously resprout after burning. shrublands of N. antarctica. The former is an obligate seed reproducer, whereas the latter and all other woody dominants of the shrubland vigorously resprout after burning. the latter and all other woody dominants of the shrubland vigorously resprout after burning. We installed fenced plots to exclude livestock and European hares from severely burned subalpine forests of Nothofagus pumilio and adjacent tall shrublands of N. antarctica. The former is an obligate seed reproducer, whereas the latter and all other woody dominants of the shrubland vigorously resprout after burning. the latter and all other woody dominants of the shrubland vigorously resprout after burning. shrublands of N. antarctica. The former is an obligate seed reproducer, whereas the latter and all other woody dominants of the shrubland vigorously resprout after burning. the latter and all other woody dominants of the shrubland vigorously resprout after burning. Nothofagus pumilio and adjacent tall shrublands of N. antarctica. The former is an obligate seed reproducer, whereas the latter and all other woody dominants of the shrubland vigorously resprout after burning. the latter and all other woody dominants of the shrubland vigorously resprout after burning. N. antarctica. The former is an obligate seed reproducer, whereas the latter and all other woody dominants of the shrubland vigorously resprout after burning. Results: Repeated measures ANOVA of annual measurements over the 2001- 2006 period indicate that cattle and hare exclusion had significant but complex effects on the cover of graminoids, forbs, climber species and woody species in the two burned community types. Significant interactions between the effects of cattle and hares varied by plant life forms between the two communities, which implies that their synergistic effects are community dependent. 2006 period indicate that cattle and hare exclusion had significant but complex effects on the cover of graminoids, forbs, climber species and woody species in the two burned community types. Significant interactions between the effects of cattle and hares varied by plant life forms between the two communities, which implies that their synergistic effects are community dependent. Repeated measures ANOVA of annual measurements over the 2001- 2006 period indicate that cattle and hare exclusion had significant but complex effects on the cover of graminoids, forbs, climber species and woody species in the two burned community types. Significant interactions between the effects of cattle and hares varied by plant life forms between the two communities, which implies that their synergistic effects are community dependent. Conclusions: Following severe fires, the combined effects of cattle and hares inhibit forest recovery and favour transition to shrublands dominated by resprouting woody species. This herbivore-induced trend in vegetation structure is consistent with the hypothesis that the effects of exotic herbivores at recently burned sites contribute to an increase in the overall flammability of the Patagonian landscape. inhibit forest recovery and favour transition to shrublands dominated by resprouting woody species. This herbivore-induced trend in vegetation structure is consistent with the hypothesis that the effects of exotic herbivores at recently burned sites contribute to an increase in the overall flammability of the Patagonian landscape. Following severe fires, the combined effects of cattle and hares inhibit forest recovery and favour transition to shrublands dominated by resprouting woody species. This herbivore-induced trend in vegetation structure is consistent with the hypothesis that the effects of exotic herbivores at recently burned sites contribute to an increase in the overall flammability of the Patagonian landscape.